The various sources of household income of paddy farmers in East Kalimantan, Indonesia - KARMINI KARMINI; KARYATI KARYATI (Society for Indonesian Biodiversity, 2018)
Karmini, Karyati. 2018. The various sources of household income of paddy farmers in East Kalimantan, Indonesia. Biodiversitas 19: 357-363. Some reports showed that agricultural and non-agricultural activities contribute to farmer household income. The objectives of this study were to identify the various sources of household income of paddy farmers, the average amount of every source of income, and the contribution of paddy farm income and non-paddy farm income to household income. This study was conducted in East Kalimantan Province, Indonesia. The two-stage cluster sampling was applied to select the study areas. The number of respondents was 380 paddy households. Descriptive statistics were used to explore, summarize, and describe the data. The sources of household income of paddy farmers in the study areas are from paddy farm income and non-paddy farm income. Paddy farm income is income from paddy farming. Non-paddy income is income from non-paddy farming jobs such as annual crops farmer, perennial crop farmer, employee, seller, fisherman, breeder of livestock, carpenter, and laborer. The average paddy farm income, non-paddy farm income, and total household income of paddy farmers in East Kalimantan in 2013 was Rp. 13,487,069.21 year-1, Rp. 20,920,464.31 year-1, and Rp. 27,360,640.28 year-1, respectively. The contribution of paddy farm income and non-paddy farm income to household income of paddy farmers was 49.29% and 50.71%, respectively.